Germinal Center Alloantibody Responses Mediate Progression of Chronic Allograft Injury - Chhabra, Manu; Alsughayyir, Jawaher; Qureshi, M. Saeed; Mallik, Mekhola; Ali, Jason M.; Gamper, Ivonne; Moseley, Ellen L.; Peacock, Sarah; Kosmoliaptsis, Vasilis; Goddard, Martin J.; Linterman, Michelle A.; Motallebzadeh, Reza; et al. (Frontiers in Immunology, 2019)
Different profiles of alloantibody responses are observed in the clinic, with those that persist, often despite targeted treatment, associated with poorer long-term transplant outcomes. Although such responses would suggest an underlying germinal centre (GC) response, the relationship to cellular events within the allospecific B cell population is unclear. Here we examine the contribution of germinal centre (GC) humoral alloimmunity to chronic antibody mediated rejection (AMR). A murine model of chronic AMR was developed in which T cell deficient (Tcrbd−/−) C57BL/6 recipients were challenged with MHC-mismatched BALB/c heart allografts and T cell help provided by reconstituting with 103 ‘TCR75’ CD4 T cells that recognise self-restricted allopeptide derived from the H-2Kd MHC class I alloantigen. Reconstituted recipients developed Ig-switched anti-Kd alloantibody responses that were slow to develop, but long-lived, with confocal immunofluorescence and flow cytometric characterisation of responding H-2Kd-allospecific B cells confirming persistent splenic GC activity. This was associated with T follicular helper (TFH) cell differentiation of the transferred TCR75 CD4 T cells. Heart grafts developed progressive allograft vasculopathy, and were rejected chronically (MST 50 days), with explanted allografts displaying features of humoral vascular rejection. Critically, late alloantibody responses were abolished, and heart grafts survived indefinitely, in recipients reconstituted with Sh2d1a−/− TCR75 CD4 T cells that were genetically incapable of providing TFH cell function. The GC response was associated with affinity maturation of the anti-Kd alloantibody response, and its contribution to progression of allograft vasculopathy related principally to secretion of alloantibody, rather than to enhanced alloreactive T cell priming, because grafts survived long-term when B cells could present alloantigen, but not secrete alloantibody. Similarly, sera sampled at late time points from chronically-rejecting recipients induced more vigorous donor endothelial responses in vitro than sera sampled earlier after transplantation. In summary, our results suggest that chronic AMR and progression of allograft vasculopathy is dependent upon allospecific GC activity, with critical help provided by TFH cells. Clinical strategies that target the TFH cell subset may hold therapeutic potential.